ANALYSIS OF ACCOUNTING FOR DAMAGED PRODUCT INVENTORY AT NORA STORE, LAWE BULAN DISTRICT, SOUTHEAST ACEH REGENCY - Indra Utama (CV Naskah Aceh, 2026)
Product damage is a significant issue within companies. The negative impact of damaged products on companies is in terms of profits or earnings. The purpose of this study is to analyze the causes of product damage, record and calculate the inventory of damaged products, and analyze efforts to reduce damaged products at Nora Store for five months, from August to December 2025. This research was conducted using a descriptive quantitative research method to determine the management of damaged or expired products at Nora Store and the recording of damaged product inventory. The results showed that at Nora Store, damaged products could not be returned to the distributor, so they were immediately discarded and recorded as damaged product costs, which automatically reduced the store's profits from the sale of these beverage products.